Museums, Societies and the Creation of Value.
1 online resource (330 pages).
Keywords: Museums, Societies and the Creation of Value focuses on the ways in which museums and the use of their collections have contributed to, and continue to be engaged with, value creation processes. Including chapters from many of the leading figures in museum anthropology, as well as from outstanding early-career researchers, this volume presents a diverse range of international case studies that bridge the gap between theory and practice. It demonstrates that ethnographic collections and the museums that hold and curate them have played a central role in the value creation processes that have changed attitudes to cultural difference. The essays engage richly with many of the important issues of contemporary museum discourse and practice. They show how collections exist at the ever-changing point of articulation between the source communities and the people and cultures of the museum and challenge presentist critiques of museums that position them as locked into the time that they emerged. Museums, Societies and the Creation of Value provides examples of the productive outcomes of collaborative work and relationships, showing how they can be mutually beneficial. The book will be of great interest to researchers and students engaged in the study of museums and heritage, anthropology, culture, Indigenous peoples, postcolonialism, history and sociology. It will also be of interest to museum professionals.